Pengaruh Social Media Marketing Terhadap Purchase Intention pada Agree Mart - Azizah, Khaerunnisa Ismi; Djuwendah, Endah (Universitas Galuh, 2024)
The development of technology and the internet has brought abundant innovations to support the agricultural sector, including iOS and Android-based applications. One company that recognizes the opportunities in agricultural digitalization is PT Telkom Indonesia, with its Digital Next Business (DXB) Directorate creating Agree. Agree provides the Agree Mart platform, an e-commerce marketplace, to contribute to the well-being of farmers. One of the Agree Mart marketing systems is using social media marketing. The aim of this study is to analyze the influence of social media marketing on purchase intention in Agree Mart. This research employs a quantitative method, utilizing online survey techniques among 120 Instagram followers of Agree Mart, and data analysis using SEM-PLS. The results reveal that Instagram's social media marketing for Agree Mart significantly and positively affects the purchase intention of Agree Mart's Instagram account followers.